Names, types and uses of the masṭara in the kingdom of Castile since the 13th century - Rodriguez Diaz, Elena (Documenta & Instrumenta - Documenta et Instrumenta, 2026)
Research into Spanish manuscript and printed sources from the Middle Ages, Early Modern, and Modern Ages on the names, uses, and characteristics of the instrument known in codicology as masṭara, which result explain that is observed in medieval codices. This paper also presents three medieval Castilian manuscripts, copied between the 13th and 15th centuries, which provide diverse evidences of the use of this tool of Arabic origin. The masṭara or "pauta" was used in two different ways, as it’s described in the sources and we can verified in practice: to ruling with lead on parchment and paper, or to imprint the layout on paper. The three codices were maked in Toledo, Guadalupe, and Cuenca. Conversely, their analysis demonstrates that the technical knowledge described in the Early Modern Age came from the medieval Spanish tradition.